2022
DOI: 10.7759/cureus.25468
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Lumbar MRI for Lower Back Pain at National Guard Hospital, Jeddah: A Retrospective Cohort Study

Abstract: IntroductionMagnetic reasoning imaging (MRI) is the imaging modality of choice for detecting spinal pathologies. The study of the appropriateness of MRI utilization in Saudi Arabia is lacking. As a result, this research aims to assess the use and misuse of lumbar MRI in lower back pain (LBP) at the National Guard Hospital (NGH) in Jeddah city. MethodsThis is a retrospective cohort study that included all adult patients who had lumbar MRI for LBP at NGH in 2019. A total of 1,225 patients were included. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…MRI and EDX can often are over utilized in the setting of lumbar radicular pain syndromes [16][17][18]. Previous studies have shown discrepancies between electrodiagnostic testing and MRI results.…”
Section: Resultsmentioning
confidence: 99%
“…MRI and EDX can often are over utilized in the setting of lumbar radicular pain syndromes [16][17][18]. Previous studies have shown discrepancies between electrodiagnostic testing and MRI results.…”
Section: Resultsmentioning
confidence: 99%